Natural-Scientific Bases of Psyche Understanding in the Programs and Research Charts of Mentally ill in Podillya at the End of the ХІХ – at the Beginning of the ХХ Centur - Chekanskaya, O. A. (Psychological Prospects Journal, 2012)
The theoretical analysis of natural-scientific direction of the first programs and charts of psyche research of mentally ill in history of the Vinnytsa neuropsychiatric hospital named after O. I. Yushchenko and detection attempts of differentiation between mental affection and psychical health of population, the tasks of consultations and diagnostic work is proposed with mentally ill of the period are highlighted, the question of population’s psychic health protection of Podillya at the end of the ХІХ – at the beginning of the ХХ century is considered.
Keywords: psyche diagnostics psychical health mental illness Podillya history of psychology Psychiatric Hospital